Quality performance of ISO 9000/2001 certified contractors [electronic resource] - 273563 Gui, Hun Chuen (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Sains (Pengurusan Kontrak Pembinaan)) - Universiti Teknologi Malaysia, 2007